THE INFLUENCE OF ADVANCED TECHNOLOGIES ON MANAGEMENT CONTROL: A CASE STUDY OF A LARGE CHEMICAL COMPANY - Silva, Maria José; Oliveira, J.; Costa, L. (XX Congresso Internacional de Contabilidade e Auditoria, 2025)
The evolution of technology has transformed business operations and management practices, also with effects in the field of management control. Over recent decades, the emergence of advanced technologies has reshaped how controllers collect, process, and deliver information for decision-making. This study examines the impact of technologies such as Robotic Process Automation (RPA), the Internet of Things (IoT), and Business Intelligence and Analytics (BI&A) on management control practices, focusing on their implementation, integration, and practical use. Based on a case study of a Chemical Company, which progressively adopted these tools in its controlling department, the findings reveal a positive impact on the efficiency and effectiveness of information management processes. Controllers now benefit from improved capabilities in data collection, analysis, and information construction, leading to measurable efficiency gains. Nevertheless, the study also highlights that the role of controllers remains critical to validate and interpret the information produced, thereby supporting managers in making informed and reliable decisions.